RHAMM expression tunes the response of breast cancer cell lines to hyaluronan - Carvalho, Ana Margarida Moura Pereira Ferreira (2022)
Hyaluronan (HA) synthesis and degradation are altered during carcinogenesis leading to an increased HA content in the tumor microenvironment, which correlates with poor prognosis and treatment outcomes. The main HA receptors, CD44 and RHAMM, are also overexpressed in tumors where they activate anti-apoptotic, proliferative, invasive, and migration signaling pathways. Herein, we used a unidirectional HA gradient to investigate in a high-throughput fashion the bi-directional communication between HA and breast cancer cell lines with different surface expression of CD44 and RHAMM. We found that the expression of CD44 and RHAMM depends on the HA density: the expression of these receptors is promoted at higher HA density and RHAMM is more sensitive to these changes when compared to CD44. Blocking either CD44 or RHAMM revealed different functions on binding and recognizing HA and a compensatory expression between these two receptors that maintains protumorigenic effectors such as cortactin.